Rancang Bangun Buku Tamu Digital Berbasis Semantic Web dengan Metode Waterfall - Retno Aoktaviani, Bunga Dea; Wibowo, Agung (Jurnal Algoritma, 2025)
The advancement of technology has driven progress across various professional fields, including the administrative activities of the Indonesian Midwives Association (IBI). One of the IBI branch offices in Semarang Regency still records visitor data manually, which poses several risks such as difficulties in retrieving archives, physical damage to logbooks, and reduced administrative efficiency. This study was conducted to provide a solution to these issues. The research employed the Waterfall method, consisting of analysis, design, implementation, and testing stages. The digital guestbook system was developed as a web-based application using PHP (Hypertext Preprocessor) and a MySQL database. The integration of semantic web technology enables more advanced data processing to support analysis and decision-making. Based on eleven test scenarios using black-box testing, the system achieved 100% validity. Furthermore, data search time improved significantly—by approximately 80–90% compared to traditional manual recording. The developed application has proven effective in increasing efficiency in managing visitor data.